Iron(II) Complexes with Two New Bichalcones - Hemalatha, G.; John Merina, A.; Venkataraman, V.R.; Nagarajan , S. (Asian Journal of Chemistry, 2010)
Two new bichalcones 2´,4´-dihydroxy-5´-(2-hydroxy)cinnamoyl-2-hydroxychalcone and 2´,4´-dihydroxy-5´-(4-hydroxy-3-methoxy)cinnamoyl-4-hydroxy-3-methoxychalcone have been synthesised and characterised by IR and PMR studies. Their iron (II) complexes have been prepared and characterised by elemental analysis, IR, magnetic and conductivity measurements.